The Imperialization Of Technology Against The Values Contained In Batik Nusantara - Hasaniyah, Nur; Basri, Hasan (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS)DO - 10.18860/iconetos.v1i1.1155, 2020)
Technology has made humans to the point of an era called the modern era. Especially when the discovery of a fact that through human technology, it is able to uncover a variety of potential that has not been revealed, hidden, and suppressed in premodern society. But along with that achievement, technology has had a very significant negative impact on humans themselves, more specifically on human-made creative products such as those in batik. The purpose of this study is to describe the forms of technological imperialization of the archipelago batik, and to find out the impact resulting from the imperialization of the technology. This research uses descriptive qualitative research methods. The first source uses primary data sources in the form of batik of the archipelago and is supported by secondary data sources in the form of books that become references relating to this study. Data collection techniques in this study were observation, interviews, discussion, documentation, and literature. From the results of research conducted, the researchers obtained research results, namely: 1) The form of technological imperialization of the archipelago batik is the creation of digital printing batik cloth and the discovery of fractal batik motifs 2). The impact resulting from this realization is the collapse of historical values, local wisdom, moral and spiritual values that exist in batik. Therefore, batik experienced desacralization.